2022
DOI: 10.1037/neu0000796
|View full text |Cite
|
Sign up to set email alerts
|

Back to the drawing board—The relationship between self-report and neuropsychological tests of cognitive flexibility in clinical cohorts: A systematic review and meta-analysis.

Abstract: Objective: Cognitive flexibility has been previously described as the ability to adjust cognitive and behavioral strategies in response to changing contextual demands. Cognitive flexibility is typically assessed via self-report questionnaires and performance on neuropsychological tests in research and clinical practice. A common assumption among researchers and clinicians is that self-report and neuropsychological tests of cognitive flexibility assess the same or similar constructs, but the extent of the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 123 publications
(270 reference statements)
1
12
0
Order By: Relevance
“…97 Our group was the first to undertake two comprehensive meta-analyses that investigated the relationship between a range of self-report and neuropsychological assessments of cognitive flexibility. In both clinical 33 and nonclinical 32 cohorts, we found little-to-no relationship between self-report and neuropsychological assessments of cognitive flexibility. However, a recent study with a large sample (n = 246) of non-clinical, younger adults reported a small, but significant relationship (r = À0.22) between the CFS and the WCST (perseverative errors).…”
Section: Summary Of Findingsmentioning
confidence: 61%
See 1 more Smart Citation
“…97 Our group was the first to undertake two comprehensive meta-analyses that investigated the relationship between a range of self-report and neuropsychological assessments of cognitive flexibility. In both clinical 33 and nonclinical 32 cohorts, we found little-to-no relationship between self-report and neuropsychological assessments of cognitive flexibility. However, a recent study with a large sample (n = 246) of non-clinical, younger adults reported a small, but significant relationship (r = À0.22) between the CFS and the WCST (perseverative errors).…”
Section: Summary Of Findingsmentioning
confidence: 61%
“…There is a building body of evidence that, although these self-report and neuropsychological assessments both purport to be capturing ‘cognitive flexibility’, they are unlikely to be tapping into shared, or similar, constructs. 32 , 33 In people with and without fibromyalgia, there appears to be a lack of association between self-reported cognitive and behavioural flexibility (i.e. Shift subscale of the BRIEF) and neuropsychological tests of cognitive flexibility (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this study used a self-report assessment of cognitive flexibility. It is well known that self-report and neurocognitive assessments of cognitive flexibility do not relate well [ 3 , 47 , 48 , 49 ]; hence, the findings of this study cannot be generalised beyond self-reported cognitive flexibility. Future research may wish to replicate the current study using a neurocognitive task of cognitive flexibility.…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, it is possible that self-reported task-switching ability is not a key correlate of NSSI among people who are highly vulnerable to emotion dysregulation (e.g., persons with BPD). Nonetheless, a recent meta-analysis found that self-reported measures of cognitive flexibility were poor proxies for performance in task-switching behavioral paradigms among clinical cohorts (Howlett et al, 2022). Thus, it is unclear if perceived task-switching ability maps on to objective performance for persons with SITB, particularly under conditions that often precipitate these problems (e.g., emotional distress).…”
Section: Resultsmentioning
confidence: 99%
“…Relatedly, factors associated with older age may also enhance cognitive flexibility (e.g., greater knowledge and life experiences related to a given task demand; Ionescu, 2012). Second, we found that researchers used a wide variety of assessment tools to measure and score cognitive flexibility—many of which demonstrate low correlations with each other (e.g., Stroop, verbal fluency, and WCST; Delis et al, 2001; Howlett et al, 2022; Whiteside et al, 2016). Lastly, none of the studies we reviewed assessed participants’ motivation or effort to perform well in task-switching and generative flexibility paradigms.…”
Section: Discussionmentioning
confidence: 99%